PERLINDUNGAN BAGI PENCIPTA KARYA LAGU YANG DICOVER DAN DIPUBLIKASI DI DIGITAL MUSIC PLATFORM: Protection for Creators of Covered and Published Songs on Digital Music Platforms - Muhammad Fadzieka Tahir Abdullah; Simona Bustani (Reformasi Hukum Trisakti, 2025)
The advancement of digital technology has significantly impacted the distribution and consumption of creative works, including music and songs. Digital platforms such as music streaming services, social media, and websites have become the primary mediums for creators to widely publish their works. While providing benefits like promotion and economic income, digitalization also presents new challenges, such as increasingly complex copyright infringements. This study aims to explore the challenges and opportunities of copyright protection in the digital era, focusing on the implementation of Law Number 28 of 2014 on Copyright in the context of digital music platforms. A normative research method with a descriptive-analytical approach was employed, analyzing primary, secondary, and tertiary legal materials. The findings highlight the importance of strengthening copyright protection mechanisms through collaboration between the government, electronic system providers, and the community. This study recommends strategic steps to enhance copyright protection, including optimizing the role of digital music aggregators in supporting creators and effectively resolving copyright disputes.